A unique class of duocarmycin and CC-1065 analogues subject to reductive activation - Jin, Wei (2007)
N-Acyl O-amino phenol derivatives of CBI-TMI and CBI-indole(2) are reported as prototypical members of a new class of reductively activated prodrugs of the duocarmycin and CC-1065 class of antitumor agents. The expectation being that hypoxic tumor environments, with their higher reducing capacity, carry an intrinsic higher concentration of “reducing” nucleophiles (e.g., thiols) capable of activating such derivatives (tunable N–O bond cleavage) increasing their sensitivity to the prodrug treatment. Preliminary studies indicate the prodrugs effectively release the free drug in functional cellular assays for cytotoxic activity approaching or matching the activity of the free drug, yet remain essentially stable and unreactive to in vitro DNA alkylation conditions (<0.1–0.01% free drug release), pH 7.0 phosphate buffer, and exhibit a robust half-life in human plasma (t(½) = 3 h). Characterization of a representative O-(acylamino) prodrug in vivo indicate that they approach the potency and exceed the efficacy of the free drug itself (CBI-indole(2)) indicating that not only is the free drug effectively released from the inactive prodrug, but that they offer additional advantages related to a controlled or targeted release in vivo.